STABILITY OF CHITOSAN-TRIPOLYPHOSPHATE COMPLEX-ENCAPSULATED ANTHOCYANIN AT HIGH WATER ACTIVITY - Umi Laila; Rochmadi Rochmadi; Sri Pudjiraharti; Rifa Nurhayati; Ervika Rahayu Novita Herawati; Dini Ariani; Yuniar Khasanah (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2020)
Previous study successfully conducted encapsulation of the purple-fleshed sweet potato’s anthocyanin but the study has yet to reveal the stability of encapsulated anthocyanin. Therefore, this research aims to observe the stability of encapsulated anthocyanin regarding the characteristic of low anthocyanin stability, which depends on environmental factors, such as temperature, pH, humidity, and water activity. The kinetic parameters of stability, including kinetic constant (k), reaction order, and half-life (t1/2), were also studied. Stability testing was conducted in high water activity of 0.75 and various in-cubation temperatures at 16, 25, 35, and 45°C. Un-encapsulated anthocyanin extract was also tested for its stability in the same condition in order to be compared with encapsulated anthocyanin. This study re-vealed that the encapsulated anthocyanin had lower stability than un-encapsulated anthocyanin extract. It was proven by higher kinetic constant and lower half-life of encapsulated anthocyanin for every incubation temperature which was induced by higher pH of encapsulated anthocyanin compared with anthocyanin extract. Besides, high water activity reduced glass transition temperature (Tg), in which encapsulated anthocyanin was in rubbery state. Both encapsulated anthocyanin and anthocyanin extract were degraded following the first order kinetic. Using the Arrhenius equation, it was obtained that the degradation kinetic constant of encapsulated anthocyanin was stated as k= 420.44 exp (-23.33/RT). Meanwhile, k= 1.12x106 exp (-46.70/RT) described degradation of kinetic constant of anthocyanin extract. The stability test re-vealed that the application of encapsulated anthocyanin was not suitable for wet-type food product.